Quem é o sujeito dos direitos humanos na declaração universal e na autobiografia de Eleanor Roosevelt (1950-1960) - Pereira, Fernanda Linhares (2016)
The present work aims to discuss the general theme of the subject of human rights, and in particular, search to answer the question: who is the subject of human rights in the 1950 - 1960. Therefore, the emphasis is placed both in the trajectory life and the construction of the subject as Eleanor Roosevelt in political networks that made possible the drafting of the Universal Declaration of Human Rights of 1948. A dialogue is established between the Autobiography of Eleanor Roosevelt and the Universal Declaration of Human Rights, two of the main sources used in this study. The objective is then to identify who is the subject of human rights in after World War II, starting dialogue between these two sources. At the same time make an evaluation of the historical, legal and philosophical transformations driven by new project of nascent human rights after conflicts from World War II.